2018
DOI: 10.1002/ccd.27905
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intracoronary hyperoxemic oxygen therapy in acute anterior myocardial infarction: The IC‐HOT study

Abstract: Background In the randomized AMIHOT‐II trial, supersaturated oxygen [SSO2] delivered into the left anterior descending (LAD) artery via an indwelling intracoronary infusion catheter following primary percutaneous coronary intervention (PCI) significantly reduced infarct size in patients with anterior ST‐segment elevation myocardial infarction (STEMI) but resulted in a numerically higher incidence of safety events. Objectives The IC‐HOT study evaluated the safety of SSO2 therapy selectively delivered to the lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
1
30
0
2
Order By: Relevance
“…The remarkably low adverse event rate at 30 days and 1 year in the IC-HOT trial126,127 is consistent with clinical observations regarding the effect of intracoronary hyperoxemia during reperfusion on infarct size 124126. However, the optimal level and duration of SSO 2 reperfusion is unknown.…”
Section: Limitationssupporting
confidence: 58%
See 1 more Smart Citation
“…The remarkably low adverse event rate at 30 days and 1 year in the IC-HOT trial126,127 is consistent with clinical observations regarding the effect of intracoronary hyperoxemia during reperfusion on infarct size 124126. However, the optimal level and duration of SSO 2 reperfusion is unknown.…”
Section: Limitationssupporting
confidence: 58%
“…In patients with a baseline LVEF <40%, even greater salvage was noted, with an absolute infarct size of 33.5% in controls and 23.5% in SSO 2 -treated patients. The relatively small infarct size in this STEMI population was recently confirmed by cardiac magnetic resonance imaging at 30 days in 100 anterior STEMI patients treated post-stenting with 60 mins of intracoronary SSO 2 (IC-HOT Trial) 126. The remarkably low 30-day complication rate (mortality = 0%; new onset CHF = 1%), with no significant change in these complications at 1 year,127 are consistent with a favorable clinical outcome associated with a reduction in infarct size.…”
Section: Introductionmentioning
confidence: 81%
“…The definitions of all endpoints are provided in the original publication 9 . The primary endpoint of the current study was the composite of all‐cause death or new‐onset HF or HF hospitalization at 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…The IC-HOT study was a prospective, open-label, single-arm study of 100 patients undergoing successful pPCI of an occluded LAD that found that optimized SSO 2 infusion via the LMCA was feasible and was associated with a favorable 30-day safety profile, with IS at 30 days similar to that observed in the SSO 2 therapy group in the AMIHOT II trial. 9 On the basis of this study, on April 2, 2019 the U.S. Food and Drug Administration (FDA) approved SSO 2 therapy for treatment of patients with anterior STEMI undergoing primary PCI within 6 hrs of symptom onset. 10 Late clinical outcomes after optimized SSO 2 infusion in STEMI have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 74 ] Furthermore, the IC-HOT study demonstrated that it was feasible for supersaturated oxygen to be delivered directly to the left main stem during STEMI. [ 75 ] While the TherOx system has been approved by the Food and Drug Administration for treatment of AMI, randomised trials have only been conducted in relatively small numbers of patients. Similar results have been seen for other cardioprotective interventions, which have proven to be ineffective in larger or less well selected trials.…”
Section: Alternative Targets For Cardioprotectionmentioning
confidence: 99%